2013
DOI: 10.3389/fnhum.2013.00505
|View full text |Cite
|
Sign up to set email alerts
|

Social exclusion modulates fairness consideration in the ultimatum game: an ERP study

Abstract: Previous neuroimaging research has identified brain regions activated when people’s fairness consideration changes under conditions of social exclusion. The current study used EEG data to examine the temporal process of changes in fairness consideration under social exclusion. In this study, a Cyberball game was administered to manipulate participants’ social exclusion or inclusion. Then, in the following Ultimatum game (UG), participants’ brain potentials were recorded while they received fair/unfair offers f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
69
1
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(85 citation statements)
references
References 59 publications
12
69
1
3
Order By: Relevance
“…To this extent, Wu et al (2012) proposed that non-equal offers (i.e., inferior or superior to the half-share) in the ultimatum game may constitute a particular case of social norm violation (i.e., equality expectancy violation) associated with a greater FRN effect compared to when the fairness norm is applied (i.e., a major negativity for non-equal shares than for equal shares). Two studies also found a greater P300 amplitude in response to fair offers compared to unfair offers (Wu et al, 2012;Qu et al, 2013). The authors interpreted this effect to reflect the greater motivational significance to fair shares than to unfair shares.…”
Section: Electrophysiological Correlates Of the Responder Playing Thementioning
confidence: 81%
See 4 more Smart Citations
“…To this extent, Wu et al (2012) proposed that non-equal offers (i.e., inferior or superior to the half-share) in the ultimatum game may constitute a particular case of social norm violation (i.e., equality expectancy violation) associated with a greater FRN effect compared to when the fairness norm is applied (i.e., a major negativity for non-equal shares than for equal shares). Two studies also found a greater P300 amplitude in response to fair offers compared to unfair offers (Wu et al, 2012;Qu et al, 2013). The authors interpreted this effect to reflect the greater motivational significance to fair shares than to unfair shares.…”
Section: Electrophysiological Correlates Of the Responder Playing Thementioning
confidence: 81%
“…Several studies recently investigated fairness consideration and the associated neural correlates using the ultimatum game paradigm (Polezzi et al, 2008;Campanhã et al, 2011;Wu et al, 2011Wu et al, , 2012Alexopoulos et al, 2012Alexopoulos et al, , 2013Qu et al, 2013). Overall, a greater negativity of the FRN component was found in response to unfair offers than to fair offers (Polezzi et al, 2008;Wu et al, 2011Wu et al, , 2012Alexopoulos et al, 2012Alexopoulos et al, , 2013Qu et al, 2013); and more interestingly, also in response to extra-fair offers (i.e., shares superior to half the amount of money to split) compared to fair offers (Wu et al, 2012).…”
Section: Electrophysiological Correlates Of the Responder Playing Thementioning
confidence: 91%
See 3 more Smart Citations